State-Feedback Control Design for the Cannon Stability System - Ahmad Syahril Muharom (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
Abstract— Tanks have an important role in protecting a region in the event of a battle. The tank's cannon is a very reliable weapon in warfare. However, the cannon's precision while aiming and firing targets is a concern. A control system must be created to increase the cannon's stability and precision. The state feedback control technique with a full-state observer is the control system that can manage cannon disturbances. The control system is built around three DC motors, each of which operates the cannon’s x, y, and z axes. Then performed tests for each axis at an angle of 90 degrees, The state feedback control with a full state observer can produce outstanding performance, with the time required for the cannon to reach the target angle was 0.51 seconds, and the cannon system had 0% overshoot.